Chromosome-scale assembly and quantitative trait locus mapping for major economic traits of the Culter alburnus genome using Illumina and PacBio sequencing with Hi-C mapping information - Liu, Shili; Zheng, Jianbo; Li, Fei; Chi, Meili; Cheng, Shun; Jiang, Wenping; Liu, Yinuo; Gu, Zhimin; Zhao, Jinliang (Frontiers in Genetics, 2023)
Topmouth culter (Culter alburnus) is an economically important freshwater fish with high nutritional value. However, its potential genetic advantages have not been fully exploited. Therefore, we aimed to determine the genome sequence of C. alburnus and examine quantitative trait loci (QTLs) related to major economic traits. The results showed that 24 pseudochromosomes were anchored by 914.74 Mb of the C. alburnus genome sequence. De novo sequencing identified 31,279 protein-coding genes with an average length of 8507 bp and average coding sequ ence of 1115 bp. In addition, a high-density genetic linkage map consisting of 24 linkage groups was constructed based on 353,532 high-quality single nucleotide polymorphisms and 4,710 bin markers. A total of 28 QTLs corresponding to 11 genes, 26 QTLs corresponding to 11 genes, and 12 QTLs corresponding to 5 genes were identified for sex, intermuscular spine number and body weight traits, respectively. In this study, we assembled an accurate and nearly complete genome of C. alburnus by combining Illumina, PacBio, and high-throughput Chromosome conformation capture (Hi-C) technologies. In addition, we identified QTLs that explained variances in intermuscular spine number, body weight, and sex differences in C. alburnus. These genetic markers or candidate genes associated with growth traits provide a basis for marker-assisted selection in C. alburnus.